Amino Acid Based Dynamic Metal–Biomolecule Frameworks. Issue 34 (3rd July 2013) - Joarder, Biplab; Chaudhari, Abhijeet K.; Nagarkar, Sanjog S.; Manna, Biplab; Ghosh, Sujit K.
<x xml:space="preserve">Abstract</x> On the move: Two isostructural, homochiral CuII coordination frameworks based on amino acids (D‐ and L‐PGA) were synthesized (see figure). Dynamic behavior by solid‐state structural transformation in single‐crystal‐to‐single‐crystal fashion was demonstrated. The extent of structural dynamism was shown by guest inclusion studies. Reversible sol–gel formation and anion‐tuning morphology of the compounds is also discussed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>